Efficiency and Marketing Margins Estimation of Oil Palm's Fresh Fruit Bunches (FFB) in Labuhanbatu Utara and Asahan Regency - Petrus Oktavianus Hutajulu; Diana Chalil; Surya Abadi Sembiring (Indonesian Journal of Agricultural Research, 2019)
This research study has reported different profit margin of smallholders in Labuhan Batu and Asahan which can be due to productions cost incurred by smallholders. In addition, the price of fresh fruit bunches (FFB) of oil palm offered by eachtrader is also found different. This could be the differences in efficiency and the length of marketing channels traversed by partner and non-partner samllholders. The length of marketing chain was transferred to the marketing costs incurred and the margins received, so there is share for each marketing. Therefore such study is needed to estimate the marketing margins and channels of non-partner smallholders, partner smallholders, and explasma smallholders, the marketing functions carried out by each palm oil marketing channel in Kuala Hulu, factors that help samllholders choose marketing channels, increase marketing and the efficientcy of non-partner samllholders, partner smallholders, and explasma smallholders. The data used in this study are primary as well as secondary data. The analytical method used in the Shepperds Method, Acharya and Anggarwals Method, Composite Index Method, Marketing efficiency index method and Soekartawi Method. The analysis shows that there are 2 marketing channels, identified as Channel 1 : Smallholders-Middleman_RAM-Palm Oil Mill and Channel 2 : Smallholders-Middleman-Palm Oil Mill. The study has concluded that all smallholders do selling, transporting, standardization, risk bearing, and securing market information. Regular customer, services, contracts are figured out as the major reasons marketing agents choose marketing channels. The most efficient marketing channel is partner independent samllholders with the shortest channel.